Characterizations of Rarely g-Continuous Multifunctions - Caldas, M.; Jafari, S.; Noiri, T. (Sarajevo Journal of Mathematics, 2024)
In 1979, Popa [15] introduced the notion of rare continuity. Quite recently, the authors [3] introduced and investigated a new class of functions called rarely g-continuous functions as a generalization of both rare continuity and weak g-continuity [5]. In this paper, we introduce and study the new notion of upper (lower) rarely g-continuous multifunctions as a generalization of upper (lower) weakly continuous multifunctions [13]. 2000 Mathematics Subject Classification. 54C60, 54C08; Secondary: 54D05